HUBUNGAN KUALITAS BAKTERIOLOGIS AIR SUMUR GALI DENGAN KEJADIAN DIARE DI KELURAHAN WAIHAONG KOTA AMBON - Rajid Fariz Rasako; Tri Joko; Hanan Lanang Dangiran (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Water plays an important role for human life, animals, plants and other bodies. The incidence of waterborne diarrhea is a major medium in the transmission of diarrhea, in addition to food and vectors. Diarrhea can occur when a person consumes drinking water that has been contaminated, either polluted from the source or polluted during the trip up to the house. The number of cases of diarrhea in Waihaong urban village from 2013 to 2015 has increased the number of cases. The high incidence of diarrhea with the coverage of digging wells contaminated with Escherichia coli bacteria can affect families who use dug wells as a means of clean water and drinking water. The purpose of this research is to analyze the relationship between bacteriological quality of dug well water and diarrhea occurrence. This research uses explanatory research type with cross sectional approach. The population in this study is the family who uses dug wells as a means of clean water with the number of 38 families using dug wells then the samples taken as a whole family using dug wells with exhaustive sampling technique. Statistical analysis using chi-square with 95% confidence level. The result showed that there was a significant relationship between septic tank distance (p-value = 0,004) and dug well construction (p-value = 0,008) with bacteriological quality of dug well water, while depth of dug well showed no relation between depth and quality of bacteriological water well with the value (p-value = 0.298). For the quality of bacteriological quality of dug well water with diarrhea occurrence there is significant relation (p-value = 0,002). Suggestions that can be asked related to this research is to maintain the condition of the environment especially the clean water that is dug wells causing the occurrence of pollution and maintained its cleanliness so as not to cause the impact of water-borne diseases.